Under the face mask: Racial-ethnic minority student-athletes and mental health use. Issue 2 (17th February 2020) - Ballesteros, Jorge; Tran, Alisia G. T. T.
Abstract: Objective: To investigate racial-ethnic minority student-athletes' (REMSA) symptoms of distress (mental health need), mental health use (usage rate), and factors that influence mental health usage. Participants: There were 241 varsity athletes (African American = 108, Latinos = 66, Asian American= 67) from the American College Health Association Fall 2015 data set. Results: Seventy-eight percent of REMSA reported some form of mental health need and only 11% of these athletes in need reported using mental health services in the past year. Additionally, a binominal logistic regression was run to identify demographic and mental health predictors of mental health use. Higher stress ( β  = 1.58, OR = 3.49, p  < .01) and having upperclassman standing ( β  = 1.07, OR = 3.91, p  < .05) predicted service use for athletes. Conclusions: Mental health professionals should be aware of the high mental health need for REMSA and the low usage rate of mental health services.